Development of Gentamicin-loaded Solid lipid Nanoparticles: Evaluation of Drug Release Kinetic and Antibacterial activity against Staphylococcus aureus. (2014) - Kazemi, Donya; Salouti, Mojtaba; Rostamizadeh, Kobra; Zabihian, Arash
No abstract available